METABOLIC STRESS AND THE CARDIOVASCULAR SYSTEM: THE HIDDEN DANGERS OF DIABETES (International journal of medical sciences, 2025)
Diabetes mellitus (DM) is a chronic disorder of carbohydrate metabolism and is one of the leading causes of death and disability worldwide. Diabetes induces metabolic stress, which significantly impacts the cardiovascular system. Consequently, a large proportion of diabetic patients die due to cardiovascular complications.